International Symposium on Islamic Civilization in Southern Africa (American Journal of Islam and Society, 2007)
AwqafSA (www.awqafSA.org.za), a South African Muslim NGO, has beenin constant contact with IRCICA (the Islamic Research Centre for IslamicHistory, Art and Culture: www3.ircica.org), an affiliate of the Organization ofthe Islamic Conference, for several years regarding possible cooperation. On18 April 2005, this contact culminated in Halit Eren’s (director-general, IRCICA)meeting with a few organizations and their representatives regarding theforthcoming “International Symposium on Islamic Civilization in SouthernAfrica,” scheduled for the following year. AwqafSA and IRCICA, aware ofthe fact that very little research has been done on Islam in southern Africa,have strongly advocated holding a symposium to bring scholars, researchers,and stakeholders together to share their thoughts on their respective countriesand communities. At this meeting, it was agreed that AwqafSA would be thelocal host in partnership with IRCICA and that the University of Johannesburgwould be the third partner in this important historical venture.The symposium took place between 1-3 September 2006 at theUniversity of Johannesburg. A few months earlier, on 28 June 2006 to beexact, Ebrahim Rasool (premier, Western Cape Province) formally launchedthe symposium at Leeuwenhof, his official residence. In his short speech, hestressed the multicultural nature of South African society and the importanceof holding such a symposium in the country, a symposium that will allowparticipants – particularly South Africans – to do some “rainbow gazing”and critically assess their position within South Africa. The premier was alsoone of the keynote speakers at the symposium. Essop Pahad (minister,Office of the President) connected the symposium proceedings to the AfricanRenaissance process as well as to the significant Timbuktu Project(www.timbuktufoundation.org; www.timbuktuheritage.org) spearheaded byShamil Jeppie (the University of Cape Town). He also touched upon newevidence of the influence of Islam in the Limpopo Valley, northern SouthAfrica. In his concluding remarks, he emphatically rejected Huntington’s“clash of civilizations” thesis ...